Education about the quality of groundwater for the people of Meruyung Village, Limo District, Depok - Dewi Syavitri; Ramadhani Yaniar; Yarra Sutadiwiria; Rendy Rendy; Rosmalia Ditha Nugraheni; Cahyaningratri Primadani; Suci Maharani; Lalita A'fin; Firman Herdiansyah (Universitas Muhammadiyah Magelang, 2023)
The city of Depok supports the capital city of Indonesia and experiences rapid population growth. As the population grows, the need for clean water becomes a significant concern in the area. According to data collected from 12 water samples in Cilodong District, Depok, all of them were found to be acidic and unsuitable for drinking. This community service initiative aims to provide the public with knowledge about techniques for building septic tanks that comply with regulations. Additionally, the public is educated on how to determine the characteristics of groundwater suitable for consumption. Counseling sessions were conducted at the Meruyung Village Office in Limo District, Depok City, and were attended by 26 Meruyung Village residents. The results of the program demonstrated an increase in public understanding of groundwater quality, rising from 74.5% to 89.5%.